Analysis of Handwriting of Juveniles in Conflict with the Law: An Insight into Forensic Psychology - Shalinee Dwivedi; Anugya Agarwal; Pooja Kataria; Suneet Kumar (Indian Journal of Forensic Medicine and Pathology, 2025)
Context: The rise in juvenile delinquency in India highlights the need for alternative methods of profiling. Graphology provides a non-invasive way to examine behavioral and emotional characteristics by analyzing handwriting. Aims: To examine the handwriting of juveniles in conflict with the law and identify psychological and behavioral indicators that may aid in forensic profiling and rehabilitation efforts. Settings and Design: A cross-sectional observational study conducted at observation homes in Prayagraj, Mirzapur, and Chitrakoot, Uttar Pradesh, involving juveniles aged 12 to 18 years. Methods and Material: Handwriting samples from 100 juveniles were assessed based on ten parameters: Slant, Baseline, Margins, Spacing, Pen Pressure, Size, Speed, Zones, Letter Formation, and Connecting Strokes. Interpretations were drawn from established graphological frameworks. Statistical analysis used: Descriptive statistics and frequency distributions were used to identify prominent handwriting features and their association with behavioral traits. Results: Inclined slants (43.3%), descending baselines (43.3%), and heavy pen pressure (76.3%) were commonly observed, correlating with emotional suppression, disillusionment, and assertiveness. Spacing patterns and zone emphasis suggested issues with trust and ambition, while slow writing speed (81.4%) indicated passivity